Peran Budaya Organisasi Bappeda Jatim dalam Meningkatkan Kompetensi ASN dan Pelayanan Digital - Zahrani, Nabila Azalia (Saraq Opat: Jurnal Administrasi Publik, 2025)
Digital transformation in governance has become a key element in shaping a modern, adaptive and responsive bureaucracy. This research explores the role of organizational culture at Bappeda East Java in increasing ASN competency capacity and improving the quality of public services in the digital governance era for regional development. Based on the organizational culture theory approach, this study identified challenges such as resistance to change and limited digital literacy of ASN, as well as opportunities in developing a collaborative, innovative, and technology-based work culture. The findings show that successful digital transformation requires a holistic approach that includes engineering organizational culture, strengthening values, norms, and work practices, and improving ASN competencies through continuous training programs. Strategic recommendations are provided to support the implementation of effective, transparent, and accountable digital governance in order to realize sustainable regional development goals.